(NoPERNAQ DRAMATURGIQ ~AJKOWSKOGO(B.s (NmOGORAFIQs - (Nb(B. (NqRUSTOWSKIJs ((NmOSKWAs (NmUZYKALNOEs, 1947)
(NrABOTA (B"(NoPERNAQ DRAMATURGIQ ~AJKOWSKOGO(B" (NBYLA NAPISANA W TE^ENIE (B1939-1940 (NG(B. (NG(B. s
Keywords: (NMONOGRAFIQs